Implementasi Decision Tree C4.5 dalam Memilih Perguruan Tinggi Pendamping Program SMK Pusat Keunggulan - Muhammad Raidinoor Pasha; Rahmat Rian Hidayat; Mohamad Ilyas Abas (STMIK Budi Darma, 2023)
The Ministry of Education, Culture, Research and Technology, the Indonesian government issued an independent learning policy episode eight, namely vocational high schools (VHS) which are centers of excellence (VHS-COE). This policy is the government's commitment to improving the quality of Indonesia's human resources. One strategy for implementing the program is to present tertiary institutions as assistants to SMKs. An appropriate selection process is needed to find relevant tertiary institutions to become Assistant Vocational High Schools. However, the current selection process still uses a platform with limited access (Google Forms). These deficiencies can lead to bias so that one cannot determine which tertiary institution is appropriate to be appointed as a companion. Therefore it is necessary to build an information system using a decision analysis approach (decision tree C 4.5) to be used as a reference in determining the eligibility of universities participating in the program. The research method uses the Software Development Life Cycle (SDLC) which is modeled using sequence diagrams and algorithms based on criteria set by the Ministry of Education, Culture, Research and Technology. The results of this study are that the management of the SMK Directorate has a more comprehensive decision-making reference for assessing which tertiary institutions are appropriate in accompanying SMKs as centers of excellence because the output results from the program have a high degree of accuracy